The e-guidebook feasibility phytoplankton in the bongkok river as learning media for plant-like protists - Armawati, Armawati; Daningsih, Entin; Candramila, Wolly (JPBIO (Jurnal Pendidikan Biologi), 2024)
The sub-topic of plant-like protists is one of the biology subjects that students still struggle to learn. Therefore, there is a need for learning media that meets these requirements and the e-guidebook. This study aims to determine the feasibility of the e-guidebook learning media based on the abundance of phytoplankton found in the Bongkok River, Tanjung Harapan Village, Kubu Raya Regency. The research method used is descriptive quantitative. The media development process involves three stages: pre-production, production, and post-production. After the media was created, the instruments and media were validated. The media validation questionnaire consists of 4 aspects (format, content, language, and practicality) with 19 criteria. The media validation was conducted by 5 validators, including 2 biology education lecturers from FKIP Untan and 3 biology teachers from grade 10 of senior high school or equivalent. The validation results were calculated using the Lawshe formula. The validation assessment received a CVI value of 1.00, thus being declared valid or feasible for further testing and can be used as a learning medium for the sub-topic of Plant-like Protists for grade 10 of senior high school or equivalent.